Quantitative analysis of the UDP‐glucuronosyltransferase transcriptome in human tissues - Lucas Zhou; Abelardo D. Montalvo; Joseph M. Collins; Danxin Wang (Pharmacology Research & Perspectives, 2023)
Abstract UDP‐glucuronosyltransferases (UGTs) are phase II drug metabolizing enzymes that play important roles in the detoxification of endogenous and exogenous substrates. The 22 human UGTs belong to four families (UGT1, UGT2, UGT3, and UGT8) and differ in their expression, substrate specificity, UDP‐sugar preference, and physiological functions. Differential expression/activity of the UGTs contributes to interperson variability in drug responses and toxicity, hormone homeostasis, and disease/cancer risks. However, in normal tissues, the tissue‐specific expression profiles and transcriptional regulation of the UGTs are still not fully understood. In this study, we comprehensively analyzed the transcriptome of 22 UGTs in 54 human tissues/regions using RNAseq data from GTEx. We then validated the findings in the liver and small intestine samples using real‐time PCR. Our results showed large interindividual variability across tissues in the expression of each UGT and the overall composition of UGT pools, consisting of different UGTs and their splice isoforms. Our results also revealed coexpression of the UGTs, Cytochrome P450s, and many transcription factors in the liver, suggesting potential coregulation or functional coordination. Our results provide the groundwork for future studies to detail further the regulation of the expression and activity of the UGTs.